Cocaine and the port: utopias of security, urban relations, and displacements of policing efforts in the port of Piraeus - Sergi, Anna (European journal of criminology, 2024)
In large commercial seaports policing and security efforts to counter the drug trade, especially cocaine, do not appear to be effective beyond a mere displacement effect. In the port of Piraeus, Greece, (perceived) rising quantities of cocaine have led to calls for further securitisation of the port to curb illicit trafficking. This article will present the current trends of countering and disrupting cocaine at the port of Piraeus and question how these efforts, together with the growth of the port, are affecting the overall territory of and around the port. This article will first argue that the (perceived) increase in cocaine trade towards/in the port of Piraeus has activated a ‘utopia of security’ in the policing and security responses at the port. This utopia of security leads to paradoxes when it comes to being effective against organised crime in the port. The article will conclude by discussing the possibility of a different approach, one of displacement of countering efforts rather than of cocaine flows. This different approach can also rebalance the focus of policing and security authorities on the relationship between the port and its territory.